ON THE AGES OF THE GALACTIC CLUSTERS NGC 188 M67 AND NGC 6791 - TORRES PEIMBERT, S (UNAM, Boletín de Observatorios Tonatzintla y Tacubaya, México., 1953)
Theoretical isochrones for three chemical compositions are presented and compared to the color-magnitude diagrams of NGC 188, M67 and NGC 6791. The metal abundances that provide the best agreement between theory and observations for NGC 188 are in the ran
BOL OBS TONAN TACUB
Keywords: AGES, GALACTIC, CLUSTERS, NGC 188, M67, NGC 6791; ASTRONOMIA Y ASTROFISICA; COSMOLOGIA Y COSMOGONIA; GALAXIAS